Pendidikan Jasmani Perspektif Ibnu Sina - Suherlan, Ano; Darajat, Amroeni; Salminawati, Salminawati (Educate: Jurnal Ilmu Pendidikan dan Pengajaran, 2022)
This article was written in order to construct physical education from the perspective of Ibn Sina. The type of writing in the article is qualitative research using library research with content analysis method as a data analysis tool. The description of the results from this article is that Ibn Sina classifies the curriculum in terms of physical aspects, character, and skills.